2015
DOI: 10.4314/ajtcam.v12i6.2
|View full text |Cite
|
Sign up to set email alerts
|

Potentials of some plant-derived foods in the management of diabetes and associated complications

Abstract: Background and Objective: Diabetes is an insidious as well as a debilitating metabolic disease with variety of causes that could lead to severe complications in multiple organs within the body system. There has been no documented scientific evidence as regards total cure of this complex chronic disease; therefore, it demands a lifelong management. This has necessitated the recent evaluation of several plant derived foods as costeffective alternatives in the management of diabetes and its associated complicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 42 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…This pharmacological and nutritional benefit of P. biglobosa has been associated with its physicochemical properties, which is perceived to act independently or in synergy; to play a pivotal role in the maintenance of normoglycemia by activating diverse protective mechanisms (Fred‐Jaiyesimi and Abo ; Ogunyinka et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…This pharmacological and nutritional benefit of P. biglobosa has been associated with its physicochemical properties, which is perceived to act independently or in synergy; to play a pivotal role in the maintenance of normoglycemia by activating diverse protective mechanisms (Fred‐Jaiyesimi and Abo ; Ogunyinka et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…Dietary proteins plays an important role in natural synthesis and maintenance of body tissues, enzymes, and hormones as well as other substances required for healthy functioning (Hayat et al 2014). Bioactive extracts isolated from medicinal plants are believed to delay, prevent, or manage metabolic diseases especially diabetes and its related complications using diverse mechanisms which could be established through their potential to increase insulin sensitivity, free radical scavenging abilities, hypolipidemic, hypoglycemic, hypocholesterolemic, antioxidative, antiinflammatory, and inhibition of α-amylase and α-glucosidase activities (Ogunyinka et al 2015). The present work is one of the series of studies trying to elucidate the mechanism of action by which protein isolate from P. biglobosa could delay or attenuate oxidative stress, while concurrently improves various tissues and organ functions affected by free radical damage in different metabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The fermented seeds of P. biglobosa are believed to possess nutritional and medicinal values; hence, they are used extensively as household spice in the preparation of various delicious foods (Ajaiyeoba 2002;Ogunyinka et al 2015). P. biglobosa belongs to the family Leguminosae and subfamily Mimosoideae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar alterations in the serum lipid of the animals suggested cardiovascular risk and that it was not completely safe for consumption. Onwuli, Bown and Ozoani (2014) and Ogunyinka et al (2015) reported that the nuts have the potential to reduce hyperglycaemia; the authors also reported that the nuts increased the haemoglobin level and decreased urine output in the test group when compared with controls and could prevent diabetes associated with renal damage.…”
Section: Anti-ulcer and Wound Healing Activitiesmentioning
confidence: 98%